(untitled) (The Agriculturists, 2013)
A study was conducted to analyze the status of fish marketing system in Parbatipur upazilla of Dinajpur district in the northwest region of Bangladesh during December 2010 to May 2011. The marketing chain from farmers to consumers in all the three fish markets was found to pass through a number of intermediaries. Four types of marketing channel were identified. The average marketing cost of retailer was 3.69 Tk/kg. The net marketing margin of the retailers for Indian major carps and Exotic carps were 8.42 and 19.17 Tk/kg, respectively. Seasonal variations in prices were observed with the highest in summer (March to May) and the lowest in winter (December to January). A number of constraints were identified. The infrastructure, transportation and packaging facilities were not satisfactory and sufficient in all the three fish markets under survey. DOI: http://dx.doi.org/10.3329/agric.v11i1.15238 The Agriculturists 2013; 11(1) 24-32